Supply Chain Success Analysis at Makeen Idea Store - Muhammad Andrian; Heny Pratiwi; Rizky Zakaryya Rasyad (Poltanesa, 2026)
This study aims to analyze the success of Supply Chain Management (SCM) implementation at Makeen Idea Store in improving operational performance and business competitiveness. This research employed a qualitative approach using a case study design, with data collected through direct observation, interviews with the store owner and employees, and documentation of operational activities. The findings indicate that the success of SCM implementation at Makeen Idea Store is influenced by several key factors, including strong information flow integration, strategic partnerships with suppliers, and demand-based inventory management. In addition, the implementation of an organized inventory recording system helps minimize errors and improve distribution efficiency. Effective SCM implementation has contributed to reducing operational costs, accelerating product distribution, and increasing customer satisfaction through stable product availability. However, several challenges remain, particularly limited digital technology adoption and dependence on certain suppliers, which may hinder sustainable supply chain performance improvement. Therefore, it is recommended that Makeen Idea Store further develop a digital-based SCM system and expand its supplier network to enhance supply chain flexibility and resilience in the future.